Efficiency of local governments in Malaysia and its correlates - Ibrahim, Fatimah Wati; Abd Karim, Mohd Zaini (Universiti Utara Malaysia, 2004)
The local government as one of the levels of government, plays a crucial role in providing public goods and services that are specific to the localities. However, the performance of local governments has been subjected to various criticisms, based on the increasing number of complaints from the public regarding provision of public goods and the poor services rendered to the locals,suggesting the ineficiency of our local governments. This article investigates this issue by analysing whether local governments in Malaysia use an eficient level of resources to provide their services. To achieve the objective, we estimate cost eficiency using the non-parametric Data Envelopment Analysis (DEA)approach. The eficiency scores were then regressed against factors that are likely to influence the local government's performance. The results indicate that the local governments in Malaysia are not fully efficient in using their inputs. The results also indicate that the variables that influence the local government's eficiency the most are level of technology usage, average income of the population, type of local government and location of the local government.